Characterization of Nano‐Titania Modified CdS /Polysulfide Electrolyte Interface by Utilizing MottSchottky and Electrochemical Impedance Spectroscopy. Issue 11 (18th September 2014) - Pareek, Alka; Paik, Pradip; Borse, Pramod H.; Aggarwal, Suresh K.
Abstract Photoelectrochemical (PEC) H2 generation is a green energy solution to upcoming energy crises. We have modified photo‐unstable CdS thin film with TiO2‐nanoparticles. Semiconductor electrolyte interface (SEI) of modified CdS surface using MottSchottky (MS) analysis is used to evaluate the relative band edge positions and flat‐band potential (VFB). Effect of applied AC‐frequency, electrolyte pH and electrode surface modification, on VFB and carrier‐concentration is studied. Modified photoanode shows high photocurrent and stability, than bare CdS photoanode. Improved performance of modified photoanode is attributed to the higher recombination lifetime of the charge carrier as deduced by electrochemical impedance spectroscopy.